2020
DOI: 10.22270/jddt.v10i3.4046
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Enhancement in Itraconazole Solubility through its Cyclodextrin-Water Soluble Polymer Ternary Inclusion Complexes

Abstract: The aim of this work is the enhancement of the hydrosolubility behaviour of a poorly soluble, weakly basic drug, using itraconazole (ITZ) as a case example. Binary inclusion complexes of ITZ with β-cyclodextrin (β-CD) are prepared in 1:2 molar ratios of ITZ to β-CD by co-evaporation method. Both solubility and dissolution behaviour are compared with that of the pure drug. Ternary complexes can be obtained by adding the polyvinylpirrolidone (PVP) which is a highly water soluble polymer, in the ITZ/ β-CD complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…It exhibits a synergistic effect between these components 23 . The Advantage of incorporating PVP K30 during the complexation of drugs with CD significantly increases the solubility and promotes the physicochemical properties of poorly water-soluble drugs 24,25 .…”
Section: Formation Of Ternary Complexmentioning
confidence: 99%
“…It exhibits a synergistic effect between these components 23 . The Advantage of incorporating PVP K30 during the complexation of drugs with CD significantly increases the solubility and promotes the physicochemical properties of poorly water-soluble drugs 24,25 .…”
Section: Formation Of Ternary Complexmentioning
confidence: 99%
“…Solid-state analyses, including Fourier transform infrared spectroscopy, powder X-ray diffraction, and differential scanning calorimetry, were performed on all formulations and pure ITZ. Solubility tests revealed that both binary and ternary complexes significantly increased ITZ solubility compared to the pure drug, with the ternary complexes showing fast and extensive drug release [ 39 ]. Cuoco et al [ 40 ] explored the impact of biomimetic media on ITZ absorption from Sporanox ® , which contains HPBCD to improve solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical modifications, such as prodrug formation, can also be employed to enhance solubility. [6][7][8][9][10] Additionally, the use of novel drug delivery systems, including lipid-based formulations, 11 nanoparticles (NP), and self-emulsifying systems, 12 has shown promise in improving the solubility of the drug and its bioavailability. 13 The formation of fibrous solid dispersions is indeed an effective approach in the field of solubility enhancement.…”
Section: Introductionmentioning
confidence: 99%